PSEUDOACROMEGALY IN A PATIENT WITH PACHYDERMOPERIOSTOSIS - Matali, Nur Husnina; Idros, Roserahayu; Lim, Kian Chai; Chong, Pui Lin (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Patients who are clinically suspected of acromegaly are usually referred to an endocrinologist. Biochemical evaluation is necessary to confirm the presence of an abnormality in the growth hormone (GH) axis. There are some conditions with physical features mimicking acromegaly in the absence of GH excess. Given the heterogeneity of conditions that can cause pseudoacromegaly, this posed a diagnostic challenge. CASE A 32-year-old male was referred to the Endocrine clinic for evaluation of suspected acromegaly. He had an incidental finding of pancytopenia and chronic excessive sweating when he presented to his General Practitioner. Following this, he was diagnosed with myelofibrosis by a haematologist. He reported having large hands and feet since his teens. He was also referred to a dermatologist for generalised skin thickening and itchiness and treated for photodermatitis. Clinically, he has clubbing of the fingers of his hands and feet and furrowing of skin on his forehead but no other phenotypical features of acromegaly. Biochemically, IGF-1 and GH levels were normal. He had a left leg X-ray followed by a CT of the left tibia and fibula for a swelling on his left lower leg, which showed wavy periosteal thickening in the tibia and fibula suggestive of hypertrophic osteoarthropathy. With a suspicion for primary hypertrophic osteoarthropathy (PHO), it was confirmed through genetic analysis that he has homozygous pathogenic variants identified in SCLO2A1 associated with an autosomal recessive PHO. CONCLUSION Primary hypertrophic osteoarthropathy, or pachydermoperiostosis (PDP), is a rare genetic disorder characterised by digital clubbing, periostosis and pachydermia. Myelofibrosis is a complication of PDP where bone marrow becomes scarred and fibrotic. In patients with features of hypertrophic osteoarthropathy and acromegaly, PDP should be considered as part of the differential diagnoses.